Stimulation of the Development of Verbal Linguistic Intelligence in Autistic Students at Muhammadiyah Elementary School 16 Surabaya - Jessica Dwi Rahmayanti; Muhamad Arif (Fitrah, 2026)
Autistic individuals experience verbal and nonverbal communication problems by 40%-50%. This disorder causes verbal-linguistic intelligence in autistic children to be very slow or absent altogether. Therefore, verbal-linguistic intelligence in autistic students needs to be developed, by providing specific stimuli. This study aims to describe the provision of stimuli in improving verbal-linguistic intelligence in autistic students at Muhammadiyah 16 Elementary School, Surabaya. This research is a qualitative research combined with a case study approach. The primary data sources in this study were the inclusion coordinator and one shadow teacher of grade II, and one shadow teacher of grade V. In collecting data, the researcher conducted overt or covert observations, semi-structured interviews, and documentation. The research instruments were interview guidelines and observation guidelines. In data analysis techniques, the researcher used data condensation, data display, conclusion drawing, and verification techniques. The results of the study showed that providing stimulus for the development of verbal linguistic intelligence in autistic students was carried out using various techniques, namely providing stimulus referring to body movements, moving objects, and saying words repeatedly, gradual assistance, using interesting learning media, visual learning media consisting of picture cards and posters, while audiovisual media in the form of children's song videos, cartoon films, gross motor exercises, providing fine motor exercises, presenting learning through storytelling, and role playing, as well as inviting autistic students to imitate animal sounds and pronounce the names of letters.